2004
DOI: 10.1007/s11145-004-2657-x
|View full text |Cite
|
Sign up to set email alerts
|

Reading and spelling error analysis of native

Abstract: This study was an investigation of reading and spelling errors of dyslexic Arabic readers (n ¼ 20) compared with two groups of normal readers: a young readers group, matched with the dyslexics by reading level (n ¼ 20) and an age-matched group (n ¼ 20). They were tested on reading and spelling of texts, isolated words and pseudowords. Two research questions were the focus of this study: What are the reading and spelling profile errors of dyslexic native Arabic speakers? What is the effect of the Arabic orthogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 43 publications
8
64
2
1
Order By: Relevance
“…Specific attention was given in several studies to the difficulty of emphatic phonemes among native Arabic speakers (Abu Rabia & Siegel, 1995;Abu Rabia & Taha, 2004Amayreh & Dyson, 1998;Ayari, 1996;Saiegh-Haddad, 2003). These aspects were extensively discussed in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specific attention was given in several studies to the difficulty of emphatic phonemes among native Arabic speakers (Abu Rabia & Siegel, 1995;Abu Rabia & Taha, 2004Amayreh & Dyson, 1998;Ayari, 1996;Saiegh-Haddad, 2003). These aspects were extensively discussed in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several scholars consider it as a second language (Ayari, 1996;Saiegh-Haddad, 2003), and native Arabic speakers as bilingual (Eviatar & Ibrahim, 2000). Previous studies have shown that the diglossic nature of Arabic affects linguistic processes, including phonological awareness, reading words and spelling among native Arabic speakers (Abu Rabia & Taha, 2004;Saiegh-Haddad, 2003, 2004. This complicated linguistic situation was also found as the main cause for low reading achievements among Arab-speaking students in Israel in PIRLS 2006 tests (Zuzovsky, 2008).…”
Section: Phonetic and Phonological Characteristics Of Arabicmentioning
confidence: 91%
See 2 more Smart Citations
“…Abu Rabia, & Taha, (2004), examined the reading and spelling errors of dyslexic Arabic readers compared to normal readers. The results of this study indicate that similar reading and spelling error profiles were observed among dyslexics and the reading-level-matched group.…”
Section: The Influence Of Arabic Orthography On Readingmentioning
confidence: 99%